Adherence to Antiretroviral Therapy Among HIV-Positive Pregnant Women on followup at Mizan Tepi University Teaching and Tepi General Hospitals, Southwest Ethiopia - Temesgen Aferu; Gatluak Doang; Ameha Zewudie; Tadesse Nigussie (SAGE Publishing, 2020)
Background: The introduction of highly active antiretroviral therapy has not only improved longevity in human immunodeficiency virus (HIV)-infected individuals but in addition has had a significant impact on the rate of mother-to-child transmission of the infection. Objective: To assess antiretroviral therapy adherence among HIV-positive pregnant women on follow-up at antiretroviral therapy clinic of Mizan Tepi University Teaching and Tepi General Hospitals. Methods: A descriptive cross-sectional study was undertaken in antiretroviral therapy clinics of Mizan Tepi University Teaching and Tepi General Hospitals from April to May 2018. Data were collected through face to face interview using structured and pretested questionnaires and analyzed using Statistical Package for Social Sciences version 20. Results: Majority of the patients had good adherence to their antiretroviral therapy, 68 (66.00%). Medication side effects, 12 (34.00%) and forgetfulness and distance of the hospital from home, each accounting 11 (31.00%) were the main reasons for nonadherence among nonadherent patients. Frequency of counseling ( P = .000), CD4 count (χ 2 = 37.529, P = .000), World Health Organization's clinical stage (χ 2 = 17.515, P = .000), stigma (χ 2 = 70.426, P = .000), and family support (χ 2 = 46.383, P = .000) were found to be associated with patients' medication adherence. Conclusion: The overall patient adherence to antiretroviral therapy in the study facilities was good. Collaborative work among patients, health care organizations, and the public are necessary to tackle the adherence obstacles and enhance patient adherence to the prescribed medication.